A Quantitative Analysis of Writing Style on the U.S. Supreme Court - Keith Carlson; Michael A. Livermore; Daniel Rockmore (Washington University Law Review, 2016)
This Article presents the results of a quantitative analysis of writing style for the entire corpus of US Supreme Court decisions. The basis for this analysis is the measure of frequency of function words, which has been found to be a useful “stylistic fingerprint” and which we use as a general proxy for the stylistic features of a text or group of texts. Based on this stylistic fingerprint measure, we examine temporal trends on the Court, verifying that there is a “style of the time” and that contemporaneous Justices are more stylistically similar to their peers than to temporally remote Justices. We examine potential “internal” causes of stylistic changes, and conduct an in-depth analysis of the role of the modern institution of the judicial clerk in influencing writing style on the Court. Using two different measures of stylistic consistency, one measuring intra-year consistency on the Court and the other examining inter-year consistency for individual Justices, we find evidence that the writing styles of individual Justices have become less consistent as clerks have taken on a greater role on the Court.
Keywords: writing; supreme court; style; quantitative; analysis